CONTINOUSLY WORKING INSTALLATION FOR SOLAR ENERGY BIOCONVERSION - Шаманський, С. Й. (Science-based technologies, 2015)
Сonversion of solar energy into biomass is one of the very important trends alternative power engineering. It cam make a significant contribution into solving the energy crisis and into solving many problems, concerning environmental safety of the economy. In the paper there is analysed advantages and disadvantages of terrestrial and aquatic plants, which can be cultivated in the process of bioconversion. There is made a conclusion, that cultivating of microalgae is one of the most prospective, because it does not require big areas of fertile land. Some of microalgae can increase their biomass way more quickly than terrestrial plants and many of them are way more rich in oils, containing much of lipids. There are also analysed known designs of photobioreactors for microalgae cultivating. There are examined devices of opened and closed design, examined their advantages and disadvantages. A conclusion is made there, that it is a topical problem to improve known designs of reactors. There is developed a new design closed photobioreactor, which is able to provide optimal conditions for cultivating different types of microalgae and can provide possibility of organising continuously going cultivation process. There are shown main advantages of proposed design for production of alternative types of fuel. Main prospectives of this design application are also outlined there.